How does internet use affect the sense of gain in older adults? A moderated mediation model - Yang, Yi; Ni, Ying (Frontiers in Psychology, 2025)
In the context of the digital era, Internet use is of major significance for enhancing the sense of gain among elderly people and enabling them to share in the development dividend of the digital society. Based on CGSS 2021 (N = 2,929), this study explores the impact of Internet use on the sense of gain in the elderly, and a moderated mediation model was constructed to explore the mediating role of perceived social justice and the potential moderating role of social status. The results showed that (1) Internet use in general significantly enhanced elderly’s sense of gain. Among this group, economic sense of gain (ESG) was significantly enhanced, political sense of gain (PSG) was positively affected but not significantly, while security sense of gain (SSG) was negatively affected. (2) A sense of social equity plays a mediating role in the impact of Internet use on the sense of gain among older adults. (3) Social status does not play a moderating role in the latter half of the path of the mediation model. Meanwhile, heterogeneity analysis revealed that Internet use positively and significantly affects the sense of gain among elderly people with low household incomes, high levels of literacy, an urban household registration, and a spouse. The research conclusion of this article provides strong empirical support for solving the problem of digital integration among the elderly and effectively enhancing their sense of achievement.